A função do coordenador pedagógico na qualificação do trabalho docente: formação continuada e avaliação educacional - Feffermann, Elizabeth (2016)
The current research investigates the Pedagogical Coordinator’s perception of his/her own formative practice, both teacher trainer and evaluator, regarding educational evaluation centered on learner’s evaluation. The research is based on qualitative research methods, and includes document analysis and interviews held with 145 pedagogical coordinators from the SESI-SP School System; three coordinators were given semi structured interviews. For the selection of pedagogical coordinators, a reference matrix was prepared taking into account the following criteria: their professional responsibilities and studies carried out by the author of the present research on the role of the pedagogical coordinator. The theoretical background needed to approach the role of the pedagogical coordinator and the teacher training process was based on the discussions put forward by Libâneo (2004), Placco (2003, 2006, 2008), Nóvoa (2005, 2009), and Almeida and Placco (2006, 2011). Freitas (2005, 2009) and Fernandes (2009) provided a useful source for the discussion on educational evaluation and the evaluative dimensions within the school. The analysis was based on the coordinator’s own account of his/her role in the school setting and his/her training performance in the context of educational evaluation, thus giving rise to four categories: The Coordinator and his/her role in the school; the Coordinator and the formative support she/he gives to the teacher; the Coordinator and his/her actions towards formative assessment in the educational evaluative process; and the Coordinator and his/her role as evaluator in the improvement of his/her work. The analysis shows that a lot must still be done concerning the Coordinator’s perception of his/her work as the professional responsible for preparing teachers for the educational evaluation. We have to keep in mind that for teachers to build their professional identity they need to incorporate the actions of an evaluator and design their own project with a critical and inquisitive eye. It becomes evident that the work done by Pedagogical Coordinators promotes changes and improvement in the process of teaching and learning, although only to a very small extent. What may be seen as a weakness or even an ambiguity in the discourse is often due to the few opportunities given for in depth discussion about these discourses so that they can become effective practices. In this scenario, an institutional policy must be enforced in order to enhance the pedagogical coordinator’s professional background and promote better structural conditions, in the hope of building better teaching practices for students